2006
DOI: 10.1103/physrevd.73.025019
|View full text |Cite
|
Sign up to set email alerts
|

Radiation reaction on charged particles in three-dimensional motion in classical and quantum electrodynamics

Abstract: We extend our previous work (see arXiv:quant-ph/0501026), which compared the predictions of quantum electrodynamics concerning radiation reaction with those of the Abraham-LorentzDirac theory for a charged particle in linear motion. Specifically, we calculate the predictions for the change in position of a charged scalar particle, moving in three-dimensional space, due to the effect of radiation reaction in the one-photon-emission process in quantum electrodynamics. The scalar particle is assumed to be acceler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…Indeed it has been shown that this formula is recovered in QED for a scalar charged particle moving on a straight line in the limit → 0 [2]. Furthermore it has been shown [3,4] that the Lorentz-Dirac radiation-reaction force [5,6,7] is obtained in the limit → 0 in QED for a scalar charged particle in three-dimensional motion under the influence of a vector potential depending only on one spacetime coordinate. (For other approaches for studying the Lorentz-Dirac force in the context of QED, see Refs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed it has been shown that this formula is recovered in QED for a scalar charged particle moving on a straight line in the limit → 0 [2]. Furthermore it has been shown [3,4] that the Lorentz-Dirac radiation-reaction force [5,6,7] is obtained in the limit → 0 in QED for a scalar charged particle in three-dimensional motion under the influence of a vector potential depending only on one spacetime coordinate. (For other approaches for studying the Lorentz-Dirac force in the context of QED, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if A (n−1) 3 tends to zero as a → 0, so does A (n) 3 . This means that all we need to show is A …”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the success of QED, some authors have explored whether its classical limit can shed light on the question of the correct theory of radiation reaction [42][43][44][45]. In [46], the QED predictions for an electron interacting with a plane electromagnetic wave have been compared with those of a range of classical theories, including LL and Sokolov.…”
Section: Introductionmentioning
confidence: 99%